2004
DOI: 10.1002/mas.20031
|View full text |Cite
|
Sign up to set email alerts
|

A new member of the hypothalamic RF‐amide peptide family, LPXRF‐amide peptides: Structure, localization, and function

Abstract: Recently, we identified a novel hypothalamic neuropeptide with a C-terminal LPLRF-amide sequence in the quail brain. This avian neuropeptide was shown to inhibit gonadotropin release from the cultured anterior pituitary. This peptide is the first hypothalamic peptide that inhibited gonadotropin release reported in vertebrates. We, therefore, termed it gonadotropin-inhibitory hormone (GnIH). After this finding, we found that GnIH-related peptides were present in the brains of other vertebrates, such as mammals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 116 publications
(187 reference statements)
2
101
0
Order By: Relevance
“…Similarly to other reports (Kriegsfeld et al, 2006;Ukena and Tsutsui, 2004), RFRP-3 cell bodies and fibers were observed throughout the diencephalon and the amygdala in the male rat. Dense networks of fibers were found in the medial amygdala (mAg), the medial preoptic area (mPOA), the bed nucleus of the stria terminalis (BnST), and the periventricular thalamic nucleus of the thalamus (PVT)-areas of the brain that are known to regulate the HPG, male sex behavior and food intake (For review see (Cunningham, Clifton, and Steiner, 1999;Fabbri, Jannini, Gnessi, Ulisse, Moretti, and Isidori, 1989;I'Anson, Foster, Foxcroft, and Booth, 1991)).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly to other reports (Kriegsfeld et al, 2006;Ukena and Tsutsui, 2004), RFRP-3 cell bodies and fibers were observed throughout the diencephalon and the amygdala in the male rat. Dense networks of fibers were found in the medial amygdala (mAg), the medial preoptic area (mPOA), the bed nucleus of the stria terminalis (BnST), and the periventricular thalamic nucleus of the thalamus (PVT)-areas of the brain that are known to regulate the HPG, male sex behavior and food intake (For review see (Cunningham, Clifton, and Steiner, 1999;Fabbri, Jannini, Gnessi, Ulisse, Moretti, and Isidori, 1989;I'Anson, Foster, Foxcroft, and Booth, 1991)).…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have suggested that stimulatory neuropeptide systems, such as galanin-like peptide (GALP), are critical for maintaining reproductive physiology and behavior, but a loss of GALP expression or activity is insufficient to account for the complete loss of reproductive function in diabetic rats; these observations suggests that other inhibitory factors may be involved (Stoyanovitch, Johnson, Clifton, Steiner, and Fraley, 2005a). A recently discovered RFamide peptide family has proven to contain prime candidates to fill this role as an endogenous inhibitory factor to reproduction (Kriegsfeld, Mei, Bentley, Ubuka, Mason, Inoue, Ukena, Tsutsui, and Silver, 2006;Tsutsui, Saigoh, Ukena, Teranishi, Fujisawa, Kikuchi, Ishii, and Sharp, 2000;Ukena and Tsutsui, 2004;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, the existence of five groups within the RFamide peptide family was recognized in vertebrates, namely the neuropeptide FF (NPFF) group, the prolactin-releasing peptide (PrRP) group, the gonadotropin-inhibitory hormone (GnIH) group, the kisspeptin group and the 26RFa/QRFP group (Chartrel et al 2011;Leprince et al 2013). These RFamide peptides have been shown to exert important neuroendocrine, behavioral, sensory and autonomic functions (Ukena & Tsutsui 2005;Tsutsui & Ukena 2006). Among those, NPFF is well known as a morphine modulatory peptide (Panula et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the existence of five groups within the RFamide peptide family has been recognised in vertebrates, namely the neuropeptide FF (NPFF) group, the prolactin-releasing peptide (PrRP) group, the gonadotropin-inhibitory hormone (GnIH) group, the kisspeptin group, and the 26RFa/QRFP group (Chartrel et al 2011;Leprince et al 2013). These RFamide peptides have been shown to exert important neuroendocrine, behavioural, sensory and autonomic functions (Ukena & Tsutsui 2005;Tsutsui & Ukena 2006).…”
Section: Introductionmentioning
confidence: 99%